Risk analysis and the security survey - Broder, James F.; Tucker, Eugene (Waltham, MA : Butterworth-Heinemann, 2012)
As there is a need for careful analysis in a world where threats are growing more complex and serious, you need the tools to ensure that sensible methods are employed and correlated directly to risk. Counter threats such as terrorism, fraud, natural disasters, and information theft with the Fourth Edition of Risk Analysis and the Security Survey. Broder and Tucker guide you through analysis to implementation to provide you with the know-how to implement rigorous, accurate, and cost-effective security policies and designs. This book builds on the legacy of its predacessors by updating and covering new content. Understand the most fundamental theories surrounding risk control, design, and implementation by reviewing topics such as cost/benefit analysis, crime prediction, response planning, and business impact analysis--all updated to match today's current standards. This book will show you how to develop and maintain current business contigency and disaster recovery plans to ensure your enterprises are able to sustain loss are able to recover, and protect your assets, be it your business, your information, or yourself, from threats. *Offers powerful techniques for weighing and managing the risks that face your organization *Gives insights into universal principles that can be adapted to specific situations and threats *Covers topics needed by homeland security professionals as well as IT and physical security managers.
Part I: The Treatment and Analysis of Risk Chapter 1: Risk Chapter 2: Vulnerability and Threat Identification Chapter 3: Risk Measurement Chapter 4: Quantifying and Prioritizing Loss Potential Chapter 5: Cost/Benefit Analysis Chapter 6: Other Risk Analysis Methodologies Chapter 7: The Security Survey: An Overview Chapter 8: Management Audit Techniques and the Preliminary Survey Chapter 9: The Survey Report Chapter 10: Crime Prediction Chapter 11: Determining Insurance Requirements Part II: Emergency Managment and Business Continuity Planning Chapter 12: Emergency Management: A Brief Introduction Chapter 13: Mitigation and Preparedness Chapter 14: Response Planning Chapter 15: Business Impact Analysis Chapter 16: Business Continuity Planning Chapter 17: Plan Documentation Chapter 18: Crisis Management Planning for Kidnap, Ransom, and Extortion Chapter 19: Monitoring Safeguards Chapter 20: The Security Consultant Appendix A: Security Survey Work Sheets Appendix B: Sample Kidnap and Ransom Contingency Plan Appendix C: Security Systems Specifications.
Machine generated contents note: Part I: The Treatment and Analysis of Risk Chapter 1: Risk Chapter 2: Vulnerability and Threat Identification Chapter 3: Risk Measurement Chapter 4: Quantifying and Prioritizing Loss Potential Chapter 5: Cost/Benefit Analysis Chapter 6: Other Risk Analysis Methodologies Chapter 7: The Security Survey: An Overview Chapter 8: Management Audit Techniques and the Preliminary Survey Chapter 9: The Survey Report Chapter 10: Crime Prediction Chapter 11: Determining Insurance Requirements Part II: Emergency Managment and Business Continuity Planning Chapter 12: Emergency Management: A Brief Introduction Chapter 13: Emergency Response Planning Chapter 14: Business Continuity Planning Chapter 15: Business Impact Analysis Chapter 16: Plan Documentation Chapter 17: Crisis Management Chapter 18: Monitoring Safeguards Chapter 19: The Security Consultant.
Description based on print version record.
Keywords: Industries -- Security measures; Risk management; Crime prevention surveys; Assistance in emergencies -- Planning; BUSINESS & ECONOMICS / Corporate Governance; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Organizational Development; BUSINESS & ECONOMICS / Workplace Culture; Electronic books